Modeling of Energy Harvesting for Wireless Sensor Network - RASOOL, FAHAD (2018)
Wireless sensor networks (WSNs), which consist of sensor nodes that are deployed over an area for monitoring purposes, are gaining attention these days. The energy harvesting wireless sensor networks (EH-WSNs) are replacing battery powered wireless sensor networks (BP-WSNs) due to the latter‟s limited lifespan. However, the models of BP-WSNs cannot be applied to EH-WSNs due to their different energy characteristics. Therefore, its modeling is now required. The EH-WSN consists of energy harvesting and energy storage subsystems.